Guidelines for Proactive Activity Development to Prevent Children and Youth from Entering into Criminal Acts: Juvenile and Family Court in Samut Sakhon - Subtaweevasin , Pornchai; Kangsadanporn, Korn (Journal of Dhamma for Life, 2025)
This research aims to study the proactive activities and present the guidelines for proactive activity development of the Juvenile and Family Court in Samut Sakhon Province. This is qualitative research that collected the data through in-depth interviews and focus groups from key informants included the former Chief Justice of the Juvenile and Family Court, judges, civil servants and psychologists, and associate judges. The results of the study found that the proactive activities of the Juvenile and Family Court in Samut Sakhon Province arose from the integrated participatory project between the Juvenile and Family Court, the Associate Justice Affairs, and schools in the area, namely the Winged Teen Activity. This was an activity that focused on preventing youth from committing criminal acts through a learning process, which emphasized learners’ participation and interaction with learning activities through various forms of practice. It also shows that the Winged Teen Activity effectively enhanced children and youth by (1) inspiring children and youth with various good role models; (2) child development in every dimension; (3) the use of modern media tools and technology; (4) the real problem investigation; (5) site survey for wrongdoing awareness; (6) organizing the proactive family relations activities; (7) creating activities within the court area; (8) expanding the network of proactive cooperation; and (9) increasing the activity time, reducing lectures, and focusing more on the participation. While the effective development guidelines for the proactive activity of the Juvenile and Family Court in Samut Sakhon Province included the expansion of (1) partnerships and networks; (2) activities to family institutions; (3) educational institutions; and (4) activities with communities. The suggestion from this study was to have the Associate Judges’ business organize more proactive activities for the benefit of children, youth and society. In addition, the other Provincial Juvenile and Family Courts should do more research on effective proactive activities, and disseminate, and exchange knowledge together in crime prevention committed by children and youth.